Alterations to DNA methylation patterns induced by chemotherapy treatment are associated with negative impacts on the olfactory pathway - Ho, Peh Joo (2024)
Background: Exposure to cytotoxic chemotherapy treatment may alter DNA methylation (DNAm) in breast cancer patients. Methods: We performed DNAm analysis in 125 breast cancer patients with blood drawn before and after chemotherapy, using the Illumina MethylationEPIC array. DNAm changes of 588,798 individual CpGs (including 41,207 promoter regions) were evaluated using linear regression models adjusted for monocyte proportion. Gene set enrichment analyses (GSEA) were conducted to identify key Gene Ontology (GO) biological processes or Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways associated with chemotherapy. Results were validated in a separate cohort of breast cancer patients who were treated (n = 1273) and not treated (n = 872) by chemotherapy (1808 blood, 337 saliva). Results: A total of 141 differentially methylated CpGs and 11 promoters were significantly associated with chemotherapy after multiple testing corrections in both the paired sample and single time point analyses. GSEA of promoter regions (pre-ranked by test statistics) identified six suppressed biological processes (p < 4.67e−8) related to sensory perception and detection of chemical stimuli, including smell perception (GO:0007606, GO:0007608, GO:0009593, GO:0050906, GO:0050907, and GO:0050911). The same six biological processes were significantly suppressed in the validation dataset (p < 9.02e−14). The KEGG pathway olfactory transduction (hsa04740) was also found to be significantly suppressed (p paired-samples = 1.72e−9, psingle-timepoint-blood = 2.03e−15 and p single-timepoint-saliva = 7.52e−56). Conclusion: The enrichment of imprinted genes within biological processes and pathways suggests a biological mechanism by which chemotherapy could affect the perception of smell.